STRATEGI PENINGKATAN KINERJA PENYELENGGARAAN DAN PENGELOLAAN KEPARIWISATAAN DAERAH PADA DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN BURU SELATAN - ZACHARIAS, TEHUBIJULUW (JURNAL BADATI, 2019)
This study aims to determine the strategy of improving the performance of the implementation and management of regional tourism on the Department of Tourism and Culture of South Buru Regency. This research is designed with a quantitative form and uses survey methods. The sample is determined by simple random sampling. For the first questionnaire, the whole population is determined. While for the second questionnaire, it is chosen by purposive sampling which is the person who becomes the policy maker in terms of tourism strategy in South Buru Regency ie 4 echelon II and II people. Data were analyzed by using SWOT analysis. The result of the research shows that strategy of improving the performance of the management and management of regional tourism in the Department of Tourism and Culture of South Buru Regency is based on the mapping of internal factors in the form of strengths and weaknesses as well as external factors in the form of opportunities and challenges with SO, WO, ST and WT and grand strategy types of development institutional, human and cultural resources, marketing and markets, investments and territories.Strategy, performance